Synthesis of silver–palladium Janus nanoparticles using co-sputtering of independent sources: experimental and theorical study - Martínez-Carreón, Maria J.; Solís-Pomar, Francisco; Fundora, Abel; Gutiérrez-Lazos, Claudio D.; Mejía-Rosales, Sergio; Fernández-Escamilla, Hector N.; Guerrero-Sánchez, Jonathan; Meléndrez, Manuel F.; Pérez-Tijerina, Eduardo (Beilstein Journal of Nanotechnology, 2024)
Janus-type nanoparticles are important because of their ability to combine distinct properties and functionalities in a single particle, making them extremely versatile and valuable in various scientific, technological, and industrial applications. In this work, bimetallic silver–palladium Janus nanoparticles were obtained for the first time using the inert gas condensation technique. In order to achieve this, an original synthesis equipment built by Mantis Ltd. was modified by the inclusion of an additional magnetron in a second chamber, which allowed us to use two monometallic targets to sputter the two metals independently. With this arrangement, we could find appropriate settings at room temperature to promote the synthesis of bimetallic Janus nanoparticles. The structural properties of the resulting nanoparticles were investigated by transmission electron microscopy (TEM), and the chemical composition was analyzed by TEM energy dispersive spectroscopy (TEM-EDS), which, together with structural analysis, confirmed the presence of Janus-type nanostructures. Results of molecular dynamics and TEM simulations show that the differences between the crystalline structures of the Pd and Ag regions observed in the TEM micrographs can be explained by small mismatches in the orientations of the two regions of the particle. A density functional theory structural aims to understand the atomic arrangement at the interface of the Janus particle.
Keywords: bimetallic nanoparticles; inert gas condensation; Janus nanoparticles; silver–palladium nanoparticles